Dihydromyricetin Alleviates Diabetic Neuropathic Pain and Depression Comorbidity Symptoms by Inhibiting P2X7 Receptor - Guan, Shu; Shen, Yulin; Ge, Huixiang; Xiong, Wei; He, Lingkun; Liu, Lijuan; Yin, Cancan; Wei, Xingyu; Gao, Yun (Frontiers in Psychiatry, 2019)
Diabetic neuropathic pain (DNP) and major depressive disorder (MDD) are common complications of diabetes mellitus and mutually affect each other. As a member of the ATP-gated ion channel family, P2X7 receptor is associated with the transduction of pain signal and the onset of depression. The aim of this study was to investigate the effects of dihydromyricetin (DHM) on rats with comorbid DNP and MDD. After the comorbid model was established, rat behavior changes were monitored by measuring the mechanical withdrawal threshold, thermal withdrawal latency, sugar water preference, immobility time in the forced-swim test, and open-field test parameters. The expressions of P2X7 receptor in the dorsal root ganglia (DRGs), spinal cord, and hippocampus were assessed by quantitative real-time PCR, Western blotting, and double immunofluorescence. We found that hyperalgesia, allodynia, and depressive behaviors of rats with comorbid DNP and MDD were relieved by treatment with DHM or application of a short-hairpin RNA for P2X7 receptor. The expression levels of P2X7, phosphorylated extracellular signal–regulated kinase 1/2, tumor necrosis factor α, and interleukin 1ß were increased in the DRGs, spinal cord, and hippocampus of rats in the model group but restored after DHM or P2X7 short-hairpin RNA treatment. In conclusion, P2X7 receptor in the DRGs, spinal cord, and hippocampus participates in the transduction of DNP and MDD signals. DHM seems to relieve comorbid DNP and MDD by reducing the expression of P2X7 receptor in the DRGs, spinal cord, and hippocampus and may be an effective new drug for the treatment of patients with both DNP and MDD.